2022
DOI: 10.1111/bpa.13129
|View full text |Cite
|
Sign up to set email alerts
|

The fate of interneurons, GABAA receptor sub‐types and perineuronal nets in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most common neurological disease, which is associated with gradual memory loss and correlated with synaptic hyperactivity and abnormal oscillatory rhythmic brain activity that precedes phenotypic alterations and is partly responsible for the spread of the disease pathology. Synaptic hyperactivity is thought to be because of alteration in the homeostasis of phasic and tonic synaptic inhibition, which is orchestrated by the GABA A inhibitory system, encompassing subclasses of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 179 publications
(211 reference statements)
1
9
0
Order By: Relevance
“…The impaired function of PV interneurons in hippocampal CA2 is accompanied by reduced inhibitory control in CA2, resulting in hyperexcitability of the pyramidal neurons and social memory deficits in Tg2576 mice [27]. This finding follows the general view that poor inhibitory transmission results in hyperexcitability of pyramidal cells, further lead-ing to neurotoxicity and neuronal loss [103]. The PV interneuron damage progression in AD is illustrated in Fig.…”
Section: Pv Interneuron Dysfunction In the Early Stagesupporting
confidence: 67%
“…The impaired function of PV interneurons in hippocampal CA2 is accompanied by reduced inhibitory control in CA2, resulting in hyperexcitability of the pyramidal neurons and social memory deficits in Tg2576 mice [27]. This finding follows the general view that poor inhibitory transmission results in hyperexcitability of pyramidal cells, further lead-ing to neurotoxicity and neuronal loss [103]. The PV interneuron damage progression in AD is illustrated in Fig.…”
Section: Pv Interneuron Dysfunction In the Early Stagesupporting
confidence: 67%
“…This could explain the decreases in membrane excit- There has been much less discussion about the role of the PNN in intrinsic membrane excitability. Theorizing about the function of the PNN includes regulating the localization of ion channels [249,250], binding cations [251], gating ion channels [252], anchoring ion channels, ion exchangers, and ion transporters in the plasma membrane, as well as reducing membrane capacitance by acting as an electrostatic insulator [253]. PNNs may act as local buffers of sodium and potassium ions in the extracellular space to ensure rapid ion transport [254,255].…”
Section: The Perineuronal Netmentioning
confidence: 99%
“…Although some studies suggest that GABAergic neurons are more resistant to neurodegeneration in AD [121,122] relative to cholinergic and glutamatergic neurons, others have reported that aberrant brain GABA levels are present in AD and mood disorders as well as in normal ageing [123][124][125][126]. Furthermore, evidence suggests a selective vulnerability of inhibitory interneurons during the disease progression of AD [127,128]. Therefore, there is scope for the development of drugs that can preferentially bind to specific subunits of the GABA A R family that will have fewer ADRs than the current benzodiazepines used clinically.…”
Section: Insights Into More Targeted Therapy For Nps In Admentioning
confidence: 99%